Methicillin-resistant Staphylococcus aureus in a Turkish hospital: characterization of clonal types and antibiotic susceptibility - Serdar Güngör; Alper Karagöz; Nadir Koçak; Tutku Arslantaş (Journal of Infection in Developing Countries)
Introduction: The assessment of the clonal spread of methicillin resistant Staphylococcus aureus (MRSA) in nosocomial and community-acquired infections through characterization of the isolates is critical for tracking the evolution of the epidemics, implementing effective control measures, and preventing future outbreaks of MRSA. In this context, it is aimed with this study to determine the clonal relationships between the S. aureus isolates obtained from the patients receiving treatment in the intensive-care units of a state hospital in Turkey.